1981
DOI: 10.1111/j.1365-2125.1981.tb01205.x
|View full text |Cite
|
Sign up to set email alerts
|

The combination of nifedipine and propranolol in the management of patients with angina pectoris.

Abstract: 1 A double‐blind cross over study was carried out to assess the effects of the combination of nifedipine and propranolol in 25 patients with chronic stable angina pectoris at beta‐adrenoceptor blockade. 2 Efficacy was judged objectively by a standardized exercise protocol using a bicycle ergometer and subjectively by patient assessment of anginal attack rate. 3 The combination of nifedipine and propranolol was shown to be effective with an increase in exercise time to angina and an increase in physical work ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The decrease in systemic blood pressure and sympathetic activation observed in the present study suggest that the addition of a I-adrenoceptor blocking drug to nicardipine to counter such reflex effects ought to be considered. The use of concurrent slow-calcium and ,-adrenoceptor blockade in angina pectoris has been advocated (Ekelund & Oro, 1979;Lynch et al, 1980;Tweddel et al, 1981); the haemodynamic safety of concurrent nifedipine and metoprolol has recently been demonstrated (Pfisterer et al, 1982;Nelson et al, 1984). Pending more definite studies, our observations suggest that the drug nicardipine predominantly induces peripheral vasodilatation without undue evidence of cardiac depression in the intact circulation; it would appear to be haemodynamically well-tolerated even in patients with severe coronary artery disease.…”
Section: Discussionmentioning
confidence: 64%
“…The decrease in systemic blood pressure and sympathetic activation observed in the present study suggest that the addition of a I-adrenoceptor blocking drug to nicardipine to counter such reflex effects ought to be considered. The use of concurrent slow-calcium and ,-adrenoceptor blockade in angina pectoris has been advocated (Ekelund & Oro, 1979;Lynch et al, 1980;Tweddel et al, 1981); the haemodynamic safety of concurrent nifedipine and metoprolol has recently been demonstrated (Pfisterer et al, 1982;Nelson et al, 1984). Pending more definite studies, our observations suggest that the drug nicardipine predominantly induces peripheral vasodilatation without undue evidence of cardiac depression in the intact circulation; it would appear to be haemodynamically well-tolerated even in patients with severe coronary artery disease.…”
Section: Discussionmentioning
confidence: 64%
“…The value of P-adrenoceptor antagonists in the management of angina pectoris (Braun et al, treatment of angina pectoris is well established 1985; Fox et al, 1980;Tweddel et al, 1981). (Kostis et al, 1985;Alderman et al, 1975; However, following oral administration nifedipine Jackson et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Tex et al found that of 52 patients who had chronic stable angina only four could not tolerate this combination clinically. Tweddel et al [78] confirmed these results and showed convincingly that propranolol plus nifedipine is a viable therapeutic alternative. Schmidt found that metoprolol in combination with nifedipine was highly effective [75].…”
Section: Chronic Stable Anginamentioning
confidence: 60%